Safety profile of sodium glucose co-transporter 2 (SGLT2) inhibitors: A brief summary - Mascolo, Annamaria; Di Napoli, Raffaella; Balzano, Nunzia; Cappetta, Donato; Urbanek, Konrad; De Angelis, Antonella; Scisciola, Lucia; Di Meo, Irene; Sullo, Maria Giuseppa; Rafaniello, Concetta; Sportiello, Liberata (Frontiers in Cardiovascular Medicine, 2022)
A new therapeutic class of oral agents firstly used for the treatment of type 2 diabetes mellitus is represented by gliflozines or sodium-glucose co-transporter 2 (SGLT2) inhibitors. SGLT2 inhibitors might be effective alone or in combination with any other drugs. This therapeutic class currently includes five agents: canagliflozin, dapagliflozin, empagliflozin, ertugliflozin, and sotagliflozin. SGLT2 inhibitors prevent the renal reabsorption of filtered glucose and sodium by blocking the SGLT2 co-transporters in the proximal convoluted renal tubule, facilitating glucose excretion in the urine (glycosuria) and lowering blood glucose levels. SGLT2 inhibitors have also shown to have pleiotropic effects and determine cardiovascular and renal prevention, thus leading to an extension of their therapeutic indication to include the heart failure. Despite their clinical benefits, warnings about adverse events have been implemented by Regulatory Agencies in the product's information since their introduction to the market. In particular, SGLT2 inhibitors have shown a strong impact on a high number of risk factors. They can cause hypoglycaemia, hypotension, lower limb amputation, fractures, genito-urinary infections, and diabetic ketoacidosis with different frequencies of onset. Despite some of these events are rare, they can lead to serious and dangerous complications, highlighting the importance of a strict monitoring of patients. Overall, SLGT-2 inhibitors are effective antidiabetic drugs with favorable advantages in renal and cardiovascular protection, and with a generally well-tolerated safety profile. This review aims to summarize the safety profile of SGLT2 inhibitors available in the market.